The influence of the impact of biotechnological radioprotective drugs on the antitumor effect of experimental radiation therapy - E. V. Murzina; E. I. Fedoros; E. D. Ermakova; N. V. Aksenova; E. V. Vorobeychikov; A. S. Simbirtsev; G. A. Sofronov (Сибирский научный медицинский журнал, 2025)
Exposure to ionizing radiation during antitumor radiotherapy can cause undesirable side effects. This is damage to healthy tissues and organs. The use of radioprotective drugs can provide protection for normal cells, but there are risks of their negative impact on the antitumor effect of radiotherapy. The aim of the work is to study the possibility of using promising biotechnological radioprotective drugs to reduce the side effects of antitumor radiotherapy.Material and methods. The study was performed on model of Ehrlich’s carcinoma in BALB/c mice with experimental radiation treatment (4 Gy X-ray). Biotechnological products, developed by Russian specialists, were administered to mice before irradiation on the 12th day after the tumor was transplanted. Chitin-glucan complex extracted from Pleurotus ostreatus was administered at a dose of 500 mg/kg intragastrically, recombinant flagellin at a dose of 1 mg/kg intraperitoneally. The volume of tumor nodules was assessed at different time points during the experiment, the degree of tumor growth inhibition was calculated, and the spread of the tumor into nearby tissues was recorded.Results and discussion. The absence of stimulation of tumor growth during the use of drugs has been established. The drugs did not reduce the inhibition of Ehrlich tumor growth in mice caused by experimental X-ray treatment. In some periods of the experiment, mice with combination therapy showed a tendency to increase the effectiveness of radiation treatment by 4–6 %. The use of recombinant flagellin led to a decrease in the number of animals with a total spread of Ehrlich’s carcinoma. When using the mushroom chitin-glucan complex, there was a tendency to decrease the value of the integral dissemination score compared to control.Conclusions. It was shown that the chitin-glucan complex from the Pleurotus ostreatus and the deimmunized recombinant flagellin did not have a negative effect on the antitumor effect of radiation exposure. The possibility of their use as a means of accompanying radiotherapy of tumors has been experimentally confirmed.